Genome analyses of amphotericin B-susceptible and -resistant strains of Leishmania (Mundinia) martiniquensis reveal variations potentially related to amphotericin B resistance - Narissara Jariyapan; Sivamoke Dissook; Pitiporn Noisagul; Patcharawadee Thongkumkoon; Chonlada Mano; Romteera Kittichaiworakul; Anuluck Junkum; Adisak Tantiworawit; Pascale Pescher; Gerald F. Späth; Hatim Almutairi; Padet Siriyasatien (Current Research in Parasitology and Vector-Borne Diseases)
Amphotericin B deoxycholate (AmpB) is used for the treatment of leishmaniasis caused by Leishmania (Mundinia) martiniquensis in Thailand, and relapse cases have been documented. To date, genomic analysis of drug-resistant L. martiniquensis strains is limited. In this study, comparative genome analyses were performed with an experimentally selected AmpB-resistant L. martiniquensis (AmpBRP2i) and two cryopreserved L. martiniquensis parasite strains isolated from a patient showing differences in response to AmpB treatment, LSCM1-WT (susceptible) and LSCM1-6 (resistant). Applying the GIP genome analyses package, we identified aneuploidy and gene copy number variations in all three samples, none of which correlated with AmpB resistance. In contrast, single nucleotide variant (SNV) analyses revealed an SNV in AmpB-resistant strains introduced a premature stop codon into a putative sterol C-24 reductase gene (C24R) (LSCM1_02556) involved in the ergosterol biosynthetic pathway in Leishmania. As Leishmania AmpB resistance has previously been linked to mutations in other genes of the ergosterol biosynthesis pathway in different species of Leishmania parasites, these results suggest that C24R may serve as an additional marker of AmpB resistance in Leishmania. We further identified two missense SNVs in AmpB-resistant strains in a putative ‘ABC transporter-like/ABC transporter family’ gene (LSCM1_01856) that could be involved in drug efflux. These initial findings pave the way for future research with a larger number of isolates to confirm the genomic signature we associate here with AmpB resistance.